Exclusionary visual depiction of disabled persons in Malaysian news photographs - Ang, Pei Soo; Yeo, Siang Lee (SAGE Publications, 2018)
Disability has been perceived as a social conditioning phenomenon and a sign system marking the body and mind. Accordingly, photographs of disability could shape our cultural perceptions about disability and disabled persons. In response to this position, we engage in a critical semiotic inquiry into press photographs of disability (N = 1002) from The Star, a Malaysian mainstream English newspaper. We adapted Van Leeuwen’s (2008) social and visual actor networks to understand the visual techniques employed in depicting disabled actors in these images. The depiction is examined in relation to their absence and/or presence in these published photographs. If absent, the inclusion of non-disabled is analyzed. When present, the social categorizations of roles, grouping and specific/generic depictions are investigated. Findings reveal disabled persons have been symbolically excluded and thus, socially othered. These exclusionary strategies imply disabling journalistic practices which should be cautioned as they could could potentially undermine the advocacy for an inclusive society.